Chemical reproductive traits of diploid Bombus terrestris males: Consequences on bumblebee conservation. (7th June 2016) - Lecocq, Thomas; Gérard, Maxence; Maebe, Kevin; Brasero, Nicolas; Dehon, Lauren; Smagghe, Guy; Valterová, Irena; De Meulemeester, Thibaut; Rasmont, Pierre; Michez, Denis
Abstract: The current bumblebee decline leads to inbreeding in populations that fosters a loss of allelic diversity and diploid male production. As diploid males are viable and their offspring are sterile, bumblebee populations can quickly fall in a vortex of extinction. In this article, we investigate for the first time a potential premating mechanism through a major chemical reproductive trait (male cephalic labial gland secretions) that could prevent monandrous virgin queens from mating with diploid males. We focus our study on the cephalic labial gland secretions of diploid and haploid males of Bombus terrestris (L.). Contrary to initial expectations, our results do not show any significant differentiation of cephalic labial gland secretions between diploid and haploid specimens. Queens seem therefore to be unable to avoid mating with diploid males based on their compositions of cephalic labial gland secretions. This suggests that the vortex of extinction of diploid males could not be stopped through premating avoidance based on the cephalic labial gland secretions but other mechanisms could avoid mating between diploid males and queens.